Equal pay : exchange of good practices (Office for Official Publications of the European Communities, 2007)
Closing the gender gap is one of the key concerns highlighted in the Roadmap for equality between women and men 2006-2010, which comes in the wake of the Framework strategy on gender equality 2001-2005. An equal pay victory can be won only by acting at all levels, involving all stakeholders and focusing on all the factors that combine to create the gender pay gap. To support this effort, the European Commission has encouraged exchanges of information and good practices in the fi eld of equal pay for men and women under the fi fth Community action programme on equal opportunities (2001-2006). This takes the form of co-funding transnational projects launched by the Member States, local public authorities, NGOs, social partners, and other relevant stakeholders. These projects have focused on various equal pay issues: some dealt with the role of employers' and employees' representatives or collective bargaining, others concentrated on a specific field of activity or level of governance, and others again sought to tackle stereotypes and raise the awareness of the stakeholders. The variety of approaches adopted refl ects the intricate nature of the issue, as highlighted by all the project promoters.This publication is designed to help ensure these tools are distributed, as widely as possible, among all the key players involved in trying to close the gender pay gap, while acting as a source of inspiration and providing food for thought for future action.